2022
DOI: 10.3390/nu14071352
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evidence of Effects of Green Mandarin (Putgyul) Extract on Skin Aging: A Randomized, Double Blind, Placebo-Controlled Study

Abstract: Green mandarins are widely consumed unripe as mandarin oranges (Citrus unshiu Marcov.), which exhibit anti-inflammatory and anti-wrinkle effects by inhibiting the production of inflammatory cytokines and matrix metalloproteinase. A randomized, double-blind, placebo-controlled clinical study was performed to verify the skin improvement efficacy and safety of green mandarin extract (PTE). For the standardization of PTE, narirutin was set as a marker compound, and PTE with a constant narirutin content was prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Besides, the anti-wrinkle effect of plant extracts has recently attracted extremely interest. [33][34][35] Most aim to slow skin Independently, positive responses to the product-evaluation questionnaire administered at the end of the study confirmed consumer acceptance.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Besides, the anti-wrinkle effect of plant extracts has recently attracted extremely interest. [33][34][35] Most aim to slow skin Independently, positive responses to the product-evaluation questionnaire administered at the end of the study confirmed consumer acceptance.…”
Section: Discussionmentioning
confidence: 66%
“…Previously published studies 30–32 have primarily focused on the combination of peptides with antioxidants for the topical treatment of aging (with enhanced performance compared to antioxidants alone). Besides, the anti‐wrinkle effect of plant extracts has recently attracted extremely interest 33–35 . Most aim to slow skin aging by repairing the disruption and fragmentation of the ECM and preventing the loss of collagen and elastin.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23] Research has indicated that the application of Citrus has shown anti-inflammatory and photoaging properties in human dermal fibroblasts and keratinocytes. [24] The antioxidant properties of the phenolic compounds may help improve the skin barrier function. [25] Citrus essential oils are potentially anticipated to be employed in numerous pharmaceutical preparation such as skin-whitening ingredients in confectioneries, soap and so on, perfumery, and cosmetology with citrus-like scents.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, evaluation of any agent for the anti‐aging effects on skin largely depends on three types of strategies 9 : cell experiments, 10 animal experiments, 11 and clinical evaluations 12 . In addition, in vivo Optical Coherence Tomography (OCT) and Reflectance Confocal Microscopy are extensively used to observe skin wrinkles and evaluate anti‐aging efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…8 Thus far, evaluation of any agent for the anti-aging effects on skin largely depends on three types of strategies 9 : cell experiments, 10 animal experiments, 11 and clinical evaluations. 12 In addition, in vivo Optical Coherence Tomography (OCT) and Reflectance Confocal Microscopy are extensively used to observe skin wrinkles and evaluate anti-aging efficacy. Despite the advantages of swiftness and cost-effectiveness, cellular experiments have limitations as they cannot directly exhibit anti-aging effects on the skin, including wrinkle improvement.…”
mentioning
confidence: 99%